SCIENCE AND EDUCATION IN THE MODERN WORLD: CHALLENGES OF THE XXI CENTURY"NUR-SULTAN, KAZAKHSTAN, APRIL 2021: SCIENCE AND EDUCATION IN THE MODERN WORLD: CHALLENGES OF THE XXI CENTURY"NUR-SULTAN, KAZAKHSTAN, APRIL 2021 - Murodov, Gayrat (FILOLOGIYA UFQLARI JURNALI, 2023)
Maqolada adabiyot shinoslikmasalari tahlil va taqdit qilingan